1997
DOI: 10.1136/jnnp.62.5.542-a
|View full text |Cite
|
Sign up to set email alerts
|

A case of Machado-Joseph disease presenting with spastic paraparesis.

Abstract: Aids to the examination of the peripheral nervous system. London: Bailliere Tindall (on behalf of the Guarantors of Brain), 1986.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…Sakai and Kawakami first reported two siblings, whose parents suffered from Parkinson's disease and SCA3 respectively, which presented spastic paraplegia at the very onset. So far, a few subtype 5 families have been reported 15,16,17,24,25 . Wang et al 25 investigated the incidence of mutation in the SCA3 gene among patients clinically diagnosed as spastic paraplegia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sakai and Kawakami first reported two siblings, whose parents suffered from Parkinson's disease and SCA3 respectively, which presented spastic paraplegia at the very onset. So far, a few subtype 5 families have been reported 15,16,17,24,25 . Wang et al 25 investigated the incidence of mutation in the SCA3 gene among patients clinically diagnosed as spastic paraplegia.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Sakai reported two Japanese siblings which originally presented spastic paraparesis 15 . Subsequently, Kaneko et al 16 and Teive et al 17 found similar families, suggesting this to be a fifth subtype. In 1996, Ishikawa et al 18 described a patient presenting with pure cerebellar ataxia (type 6).…”
mentioning
confidence: 88%
“…Additional reports of families with different origins, namely, Japanese [Kaneko et al, 1997], German [Landau et al, 2000], Brazilian [Teive et al, 2001], and Chinese [Gan et al, 2009], clinically diagnosed with HSP, but presenting an expanded allele at the MJD locus (66-86 CAG repeats), were subsequently described. Moreover, the screening of the MJD mutation in a larger Chinese series of AD-HSP patients , revealed that expanded ATXN3 alleles (64-81 CAG repeats) were responsible for the disease in 13% of the studied AD-HSP families.…”
Section: Machado-joseph Disease/spinocerebellar Ataxia Typementioning
confidence: 99%
“…After that, Kaneko et al 6 described a new patient with MJD presenting as spastic paraplegia. As in our case there was a great intra-familial phenotypic variability in both two previously reported families.…”
Section: Discussionmentioning
confidence: 99%